Advance java - Kumar, Ashish (S.K. Kataria & Sons, 2012)
This book 'Advance Java' is meant for the engineering students of various universites of haryana (MDU, GJU, KUK, and CDLU) and other states. This book contains simple and easily understandable figures with examples and definitions to undersand easily what has said in the words. .